Influence of recombinant growth hormone treatment on the state of pituitary-thyroid and pituitary-adrenal systems in children with syndrome of biologically inactive growth hormone - Sprynchuk, Nataliia; Bolshova, Olena (ScienceRise: Medical Science, 2019)
Combined insufficiency of adenohypophysis such as thyrotropic and adrenocorticotropic, especially during treatment with recombinant growth hormone, were often observed among children with somatotropic insufficiency. Aim. To evaluate the adaptation mechanisms of the organism based on studying the peculiarities of pituitary-thyroid and pituitary-adrenal functions in patients with syndrome of biologically inactive growth hormone on the background of recombinant growth hormone treatment. Materials and methods. There were examined 158 patients with syndrome of biologically inactive GH (49 girls and 109 boys); the mean age of patients was 8.3 ± 0.24 years. The levels of thyrotropic hormone, thyroxine, triiodothyronine, thyroid peroxidase antibody, adrenocorticotropic hormone, and cortisol were determined. The examinations were performed before and against the recombinant growth hormone treatment for 6 months. The control group consisted of 42 healthy children (12 girls and 30 boys), the age was from 5 to 16 years. Results. The levels of thyrotropic hormone in blood plasma of children with syndrome of biologically inactive growth hormone were increased but remained within the normal range during therapy with recombinant growth hormone. Peripheral indices of thyroid function in patients with syndrome of biologically inactive growth hormone, according to free thyroxine, before treatment and against the background of the recombinant growth hormone use almost had no differences and did not reach a significant difference, although they tended to decrease compared with the control group. The levels of adrenocorticotropic hormone and cortisol in blood plasma of children with syndrome of biologically inactive growth hormone before recombinant growth hormone treatment comparing to the control group did not have significant differences. Recombinant growth hormone therapy for 6 months resulted in an increase in the values of adrenocorticotropic hormone (p<0.01) and cortisol (p <0.01) compared with those of children with syndrome of biologically inactive growth hormone before the use of recombinant growth hormone and practically consistent with the reference values. Conclusions. Syndrome of biologically inactive growth hormone is not accompanied by disorder of the thyrotropic and adenocorticotropic functions of the pituitary gland. Reserve adaptive mechanisms of pituitary-thyroid gland and pituitary-adrenal gland systems have an adequate response to long-term treatment with recombinant growth hormone drugs